Minat Siswa Putra dalam Mengikuti Ekstrakulikuler Sepakbola di Madrasah Aliyah Negeri (MAN) Buleleng - Mubarrak, Syahrul; Dharmadi , Made Agus; Kusuma , Ketut Chandra Adinata (Universitas Pendidikan Ganesha, 2024)
The research aims to determine male students' interest in participating in football extracurriculars at MAN Buleleng. The research method uses descriptive, through surveys. The research sample was 47 students. The sampling technique uses random sampling technique. Data collection was used by administering questionnaires. The data analysis technique uses the Gregory test. Based on the results of the research, it was concluded that (1) the interest of male students in taking part in football extracurricular activities at MAN Buleleng was from intrinsic factors in the high category of 59% and the low category was 41% and the interest of male students in taking part in extracurricular football activities in MAN Buleleng was from extrinsic factors in the category the high category is 54% and the low category is 46%.